Crop straw incorporation mediates the impacts of soil aggregate size on greenhouse gas emissions - Jiang, Mengdie; Yang, Niping; Zhao, Jinsong; Shaaban, Muhammad; Hu, Ronggui (Geoderma, 2021)
[Display omitted] •Soil aggregate size significantly affected CO2 and N2O emissions.•Straw addition increased CO2 and N2O emissions in each aggregate size.•N2O emission was highest from macro-aggregate (1–2 mm) in straw-amended treatments.•CO2 emission was highest from micro-aggregate (<0.25 mm) in straw-amended treatments.•Coupling of enzymic and physiochemical properties regulate CO2 and N2O emissions. Greenhouse gas (GHG) emissions from agricultural soil have been widely discussed to combat the risks of global warming. However, GHG emissions at the soil aggregate scale have yet to be elucidated, particularly in association with straw incorporation. In this study, three different sizes of soil aggregates (1–2, 0.25–1, and < 0.25 mm) were incubated in the laboratory at 25 °C for 58 days with and without rapeseed straw (Brassica napus L.) addition to determine the extent to which aggregate sizes contribute mostly to carbon dioxide (CO2) and nitrous oxide (N2O) emissions upon straw addition. Results showed that cumulative CO2 emission in < 0.25 mm fraction (546 mg C kg−1 soil) was significantly (P < 0.001) lower than that in 0.25–1 mm (810 mg C kg−1 soil) and < 1–2 mm (762 mg C kg−1 soil) fractions in straw-unamended treatments. Straw addition increased cumulative CO2 emissions by 7.2-, 5.87-, and 13.1-fold from 1 to 2, 0.25–1, and < 0.25 mm fractions, respectively, compared with those of the corresponding straw-unamended treatments. Straw addition increased cumulative N2O emissions in each size of aggregates, and cumulative N2O emissions in 1–2 mm fraction ranked the first across the straw-unamended and straw-amended treatments. The activities of β-glucosidase, β-cellobiohydrolase, N-acetyl-β-D-glucosaminidase, and leucine aminopeptidase were enhanced by straw addition in each size of aggregates, and < 0.25 mm fraction exerted the lowest enzyme activities. Structural equation modeling and redundancy analysis confirmed that the interaction between soil physiochemical parameters (nitrate nitrogen and dissolved organic C) and specific enzyme activities was the key driver for regulating CO2 and N2O emissions. These results implied that identifying the straw as a function of aggregate‐scale GHG dynamics could improve the mechanistic understanding of global warming.